Thinking migration and home-making through materialities - Azevedo, L. (IMISCOE Spring Conference 2020, 2020)
Home-building and home-making have been important elements of the migration project of most of the Portuguese migrants who moved to Switzerland in the 1980s and 1990s, but they also play an important role in the return migration. Similarly, migration has influenced peoples’ home-making in both origin and destination countries, both materially and emotionally. Besides, evidence of transnational life courses can be found in migrants’ homes, where a wide range of materialities reflects people’s cross-cultural experiences; objects constitute therefore a relevant corpus for migration researchers. In line with the perspective of the “new mobilities paradigm [that] considers the mobility of not only people but also ideas and material objects, and especially how different types of objects move in tandem or in related way” Ciobanu & Hunter (2017: 6), I will explore the home-migration nexus as well as the migration-material culture nexus. For this purpose I will use data (including pictures) from an empirical on-going research on older Portuguese migrants in Switzerland at retirement age.